Application of Value at Risk for Managing Portfolio Currencies of Transaction Exposure: A Case Study of Trade Payables in PT. United Tractors, Tbk. - Fiksriyoso, Nisham; Surya, Budhi Arta (The Indonesian Journal of Business Administration, 2013)
United Tractors has some trade payables to foreign related parties in various currencies at certain maturity. United Tractors has potential downside risk in facing unfavorable movement of the foreign exchange rates. The currencies are United States Dollar (USD), Japanese Yen (JPY), Euro (EUR), Australian DollarÃ‚Â (AUD) and Singapore Dollar (SGD), while the Company use Indonesian Rupiah (IDR) as the entityÃ¢â‚¬â„¢s functional currency. In 2011, one of subsidiaries recorded 3.6 billion IDR losses in the other comprehensive expense (derivatives). Topic of final project is concern on transaction exposure arising from trade payables regardless of what payables are being and how much units to transact. This research aims to apply and compare three approaches to VAR methodology. Delta-Normal method use Variance-Covariance to compute portfolio VAR. Historical Simulation use hypothetical values taken from historical data to obtain profit/loss distribution. Monte Carlo Simulation also provides profit/loss distribution. This method implements ItÃƒÂ´Ã¢â‚¬â„¢s lemma to accomplish lognormal distribution and Cholesky factorization to solve multiple sources of risk. FX-Forward rate calculation is corresponding to each interest risk free rate of exchange rates. Based on calculation, United Tractors should hedge all units of transaction exposure in shorter period by also considering the hedging cost. The Company may implement Monte Carlo Simulation accomplished by ItÃƒÂ´Ã¢â‚¬â„¢s lemma and Cholesky factorization to measure foreign exchange risk using VAR method. Ã‚Â Keywords: Transaction Exposure, Value at Risk, Delta-Normal, Historical Simulation, Monte Carlo Simulation, ItÃƒÂ´Ã¢â‚¬â„¢s lemma, Cholesky Factorization.